2023
DOI: 10.29303/risma.v3i3.790
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Literasi Keuangan Syariah, Pengetahuan, Religiusitas, Dan Uang Saku Terhadap Minat Mahasiswa Menjadi Nasabah Pada Bank Syariah (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Mataram)

Dhea Indah Puji Lestari,
Susi Retna Cahyaningtyas,
Zuhrotul Isnaini

Abstract: Penelitian ini bertujuan untuk menguji pengaruh literasi keuangan syariah, pengetahuan, religiusitas dan uang saku terhadap minat mahasiswa menjadi nasabah pada bank syariah (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Mataram). Penelitian ini merupakan penelitian asosiatif dengan pendekatan kuantitatif. Data yang digunakan dalam penelitian ini adalah data primer yang diperoleh melalui penyebaran kuesioner (angket) kepada responden. Sampel dalam penelitian ini adalah mahasiswa Fakultas Ekonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of this study show that service on customer does not have a significant effect on customer decisions.This research supported by Lestari et al showed that the service had no effect on customer decisions in transacting at Bank Syariah. In addition, fast and accurate service, as well as good employee courtesy behavior did not affect the increase in customer numbers (Lestari, A. ,2015). The results of the above research can conclude that the variable quality service has no significant effect on the decision of customers to save in Islamic Bank of Indonesia.…”
Section: The Effect Of Service On Customer Decisions To Keep Saving A...mentioning
confidence: 77%
“…The results of this study show that service on customer does not have a significant effect on customer decisions.This research supported by Lestari et al showed that the service had no effect on customer decisions in transacting at Bank Syariah. In addition, fast and accurate service, as well as good employee courtesy behavior did not affect the increase in customer numbers (Lestari, A. ,2015). The results of the above research can conclude that the variable quality service has no significant effect on the decision of customers to save in Islamic Bank of Indonesia.…”
Section: The Effect Of Service On Customer Decisions To Keep Saving A...mentioning
confidence: 77%